15 (NWIRTUOZNYH \T@DOW DLQ FORTEPIANO(B. (NsO^(B.72s (NNOTY(B.s - (Nm(B.(NmO[KOWSKIJ(B.s ((NsANKT(B-(NpETERBURGs (NlAN_s (NpLANETA mUZYKIs, 2019)
(NnEMECKIJ KOMPOZITOR mORIC mO[KOWSKIJ (B(1854-1925) (NWNES ZNA^ETEL_NYJ WKLAD W RAZWITIE FORTEPIANNOJ MUZYKI RUBEVA h(BI(Nh(B-(Nhh WEKOW(B.s
Keywords: (NFORTEPIANOs